A qualitative comparison of DSM depression criteria to language used by older church-going African-Americans*. (2nd September 2018) - Akinyemi, Esther; Watkins, Daphne C.; Kavanagh, Janet; Johnson-Lawrence, Vicki; Lynn, Shana; Kales, Helen C.
ABSTRACT: Objective: Depression in late life is associated with substantial suffering, disability, suicide risk, and decreased health-related quality of life. According to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), a depression diagnosis is derived from a constellation of symptoms that may be described differently by different people. For example, the DSM language may be inadequate in capturing these symptoms in certain populations such as African-Americans, whose rates of depression misdiagnosis is high. Methods: This study reports the findings from a church-based, qualitative study with older African-Americans ( n = 50) regarding the language they use when discussing depression and depression treatment, and how this compares to the DSM-IV depression criteria. Content analyses of the in-depth discussions with African-American male and female focus group participants resulted in a deeper understanding of the language they used to describe depression. This language was then mapped onto the DSM-IV depression criteria. Results: While some words used by the focus group participants mapped well onto the DSM-IV criteria, some of the language did not map well, such as language describing irritability, negative thought processes, hopelessness, loneliness, loss of control, helplessness, and social isolation. Conclusions: The focus group setting provided insight to the language used by older, church-going African-Americans to describe depression. Implications include the advantages of using qualitative data to help inform clinical encounters with older African-Americans.